Learning styles and level of achievement in the area of Math. First secondary students. IE N° 5127. Ventanilla. Callao - Espinoza Castro , Irma Noemi (2023)
When we talk about learning achievements it is unavoidable to talk about learning styles and this is the objective of the present study, to establish if there is a relationship between learning styles and the level of learning achievement. For this, a scientific investigation with a quantitative approach, hypothetical deductive method, cross section and ordinal level served as a template. A descriptive correlational design, using descriptive and inferential statisticians, served as a technique to find the results, based on the application of a questionnaire survey using the Kolb Learning Styles Inventory and a test of mathematical competencies for learning achievement in the school N. 5127 of Ventanilla, Callao, in a sample of 1st year students. secondary. Results were obtained that demonstrate a statistically significantly high r=0.765, a p less than 0.05, which demonstrate that the correlation through Spearman's Rho is positive, so that learning styles have a direct, positive and significant with the level of mathematics achievement in 1st grade students. secondary school at school N. 5127 in Ventanilla, Callao.